Evaluation of anatomic landmarks to increase precision performing a mini-hemilaminectomy—an ex vivo study in dogs - Brechbühl, Stefanie; Husi, Benjamin; Knell, Sebastian (Frontiers in Veterinary Science, 2024)
The mini-hemilaminectomy is a frequently used surgical technique for decompressive disc surgery on dogs. The aim of the study was to assess landmarks in the canine thoracolumbar spine to perform a mini-hemilaminectomy, with the aim to achieve optimal exposure of the ventral aspect of the vertebral canal. We hypothesized that the accessory process is a useful landmark for identification of the level of the vertebral canal floor and to decrease surgical time. To define the level of the vertebral canal floor, different landmarks and their distance to the vertebral canal floor from Computed Tomography images of forty mature chondrodystrophic dogs were evaluated in the first part of the study. To test the predefined landmarks, a cadaveric experiment was subsequently performed in the second part of the study. An experienced surgeon and a second-year surgical resident performed mini-hemilaminectomies as precisely as possible with and without using the landmark values. Surgery time, precision of the mini-hemilaminectomy and iatrogenic damage of the spinal nerve roots were compared between two groups. Based on the results in the first part of the study, the distance from the dorsal border of the accessory process to the vertebral canal floor (DBAP-VCF) was chosen as landmark due to the good intra-(0.96) and interobserver (0.83) agreement. However, the distance is highly variable between breeds. In the second part of the study, using the DBAP-VCF landmark value did not influence the surgery time in both surgeons (p=0.467, p >0.99). An improved accuracy of the vertebral canal floor was seen for the surgical resident with limited experience (p = 0.014), but not for experienced surgeon (p=0.926). For both surgeons, the spinal nerve roots were injured in 20% of the cases unrelated to the use of landmark values. In conclusion this study suggests the DBAP-VCF has been described as a breed specific landmark that can be determined in CT with good agreement. Using the previously evaluated landmark values can help to improve precision in decompressive spinal surgery for a surgeon with limited experience without prolonging surgical time.